LA PRESENCIA DEL GENERO AUCELLINA (BIVALVIA, CRETACICO) EN LA FORMACION HITO XIX (TIERRA DEL FUEGO, ARGENTINA) (Ameghiniana, 2013)
After a field trip made to the central portion of the main island of Tierra del Fuego, it is made a description of the Hito XIX Forrnation, of Aptian age (Lower Cretaceous). It bears an abundant Aucellina fauna, as well as other species. lt is described Aucellina radiatostriata Bonarelli, Aucellina andina Feruglio, Sphaera? striata (Richter), and also are figured Inoceramus sp. "Pecten" sp., Brachiopoda sp. indet., Belemñites sp. indet. and Rotularia callosa (Stoliczka). A discussion about the previous aucellinas described for Patagonia and Antarctica is made, and it is decided to include them all in two species (A. andina and A. radiatostriata). There are also made considerations about the life habits, and paleoecology of the genus Aucellina.